Clinical features, prognostic factors and outcome of children with ewing sarcoma: A single-center experience - Odaman Al, Işık; Demirağ, Bengü; Sabah, Dündar; Kamer, Serra; Doğan Avşargil, Başak; Argın, Mehmet; Oymak, Yeşim (Galenos Publishing House, 2023)
Introduction: Ewing sarcoma (ES) is a rare, aggressive, malignant tumor. It is the second most common malignant bone tumor in children. A total of 20-25% of patients are metastatic at the time of diagnosis. The survival rate for localized disease (LD) is approximately 70-74%. For metastatic disease (MD), it is about 30%. The most important prognostic factor affecting survival is the presence of MD at diagnosis. In this study, we investigated the clinical characteristics, treatment outcome, and factors affecting the prognosis and survival of patients followed up with the diagnosis of ES. Materials and Methods: Between 2007 and 2020, a total of 24 ES patients aged 0-18 years were retrospectively analyzed. Results: The most common complaint was pain and swelling in the lesion area (n=9), followed by pain (n=5), swelling (n=3), abdominal pain (n=2), shortness of breath (n=2), facial paralysis (n=1), spinal compression findings (leg pain and walking difficulty) (n=1) and hematuria (n=1). ES was bone-derived in 19 patients (79%). Of these, 14 had LD and 5 had MD at the time of diagnosis. Extraskeletal Ewing sarcomas (EES), was detected in five patients (21%) and derived from the kidney (n=1), rectus abdominis (n=1), left quadriceps femoris muscle (n=1), left upper thoracic region and lumbar region paraspinal muscles (n=2). The rate of MD was 25% (6/24) in the entire patient group. Disease progression was observed in three patients during treatment. Relapse at follow-up was observed in 6 of 19 patients in complete remission. The median time to relapse was 20 months (minimum 13, maximum 34 months) from diagnosis. The median survival of our patients after relapse was 14.5 months (minimum 6-maximum 27 months). Radiological response and histopathological response to induction therapy, presence of relapse or progression, and relapse site were found to be correlated with survival (Fisher’s Exact test p=0.02, 0.0047, [removed]

Giriş: Ewing sarkomu nadir görülen, agresif, malign bir tümördür. Çocuklarda görülen ikinci en sık malign kemik tümörüdür ES tanı sırasında lokal (LH) ve metastatik hastalık (MH) olarak karşımıza çıkabilir. %20-25 hasta tanı sırasında metastatiktir. LH’de sağkalım yaklaşık %70-74’tür. MH’de ise %30 civarındadır. Sağkalımı etkileyen en önemli prognostik faktör tanı sırasında MH varlığıdır. Bu çalışmamızda ES tanısı ile takip ettiğimiz hastaların klinik özelliklerini, tedavi yanıtlarını, prognozu etkileyen faktörleri ve sağkalımlarını değerlendirmeyi amaçladık. Gereç ve Yöntem: Hastanemizde 2007-2020 yılları arasında ES tanısı ile tedavi gören 0-18 yaş 24 hasta retrospektif olarak değerlendirildi. Bulgular: Başvuru şikayetleri en sık lezyon bölgesinde ağrı ve şişlik (n=9) iken, ağrı (n=5), şişlik (n=3), karın ağrısı (n=2), nefes darlığı (n=2), yüz felci (n=1), bacaklarda ağrı-yürümede zorluk yakınması ile gelen olgumuzda spinal bası bulguları (n=1) ve hematüri (n=1) hastaneye başvuru nedenleri idi. ES 19 hastada (79%) kemik kaynaklıydı. Bunların 14’ünde tanı sırasında lokal, 5’inde metastatik hastalık mevcuttu. Beş hastada (21%) ise ekstraskeletal saptanmış olup, böbrek (n=1), rektus abdominis (n=1), sol kuadriseps femoris kası (n=1), sol üst torakal bölge ve lomber bölge paraspinal kasları (n=2) kaynaklıydı. Tüm hasta grubunda MH oranı 25% (6/24) idi. Üç hastada tedavi altında progresyon görüldü. Tam remisyona giren 19 hastanın 6’sında (6/19) izlemde relaps gözlendi. Relaps zamanı tanıdan itibaren ise ortanca 20 ay (minimum 13, maksimum 34) idi. Hastalarımızın relaps sonrası yaşam süresi ortanca 14.5 ay (minimum 6-maksimum 27 ay) idi. İndüksiyon tedavisine radyolojik yanıt, indüksiyon tedavisine histopatolojik yanıt, relaps ya da progresyon varlığı ve relaps yeri sağkalım ile ilişkili olarak bulundu (Fisher’s exact test p=0,02, 0,0047, <0,001, 0,001). Sonuç: ES mortalite ve morbiditesi yüksek olan bir kanser türüdür. En sık semptom ağrı ve şişlik olmakla birlikte tümörün kaynaklandığı bölgeye göre semptomlar farklılık gösterebilir. Indüksiyon tedavisine yanıt, relaps-progresyon varlığı prognozu etkileyen faktörlerdir. Sağkalımı artırmak için tedavi kişiselleştirilmelidir.
Ewing sarkomlu çocuk hastaların klinik özellikleri, prognostik faktörleri ve tedavi sonuçları: Tek merkez deneyimi
Keywords: Bone Tumors; Children; Ewing Sarcoma; Sarcoma; Ewing Sarkom; Çocuk; Kemik Tümörleri; Sarkom